Collagen scaffold for mesencyhmal stem cell from stromal vascular fraction (biocompatibility and attachment study): Experimental paper. (November 2020) - Sananta, Panji; Rahaditya, I.G.M.O.; Imadudin, Mohamad I.; Putera, Marvin A.; Andarini, Sri; Kalsum, Umi; Mustamsir, Edi; Dradjat, Respati S.
Abstract: Background: One of the most important part of tissue engineering (TE) is a matrix called scaffold. A good scaffold integrates with the host tissue and support the growth and differentiation of the cells. Collagen is the most abundant protein in the ECM and has been considered to be a group of proteins with a characteristic molecular structure—fibrillar structure, which contributes to the extracellular scaffolding. Objective: In this research we study the biocompatibility and attachment of collagen scaffold by measuring the level of availability of mesenchymal stem cell (MSC) cluster from stromal vascular fraction (SVF). Method: This study was experimental invitro on MSC culture derived from SVF, with post-test control group design. Biocompatibility was measured by viability of MSC from SVF with marker Propidium Iodine through flowcytometry and electron microscope was used to assess the population density of MSC from SVF by measuring the number of cluster cells seen. Result: Oxidize cellulose has the greatest value of MSC cluster with average number of 2003 cell cluster. This result was significant with p < 0.05 using One-Way Anova and Tukey Test. Conclusion: Collagen scaffold is ideal for MSC from SVF because of its compatibility and attachment. Highlights: Biocompatibility and attachment of collagen scaffold. Measuring the level of availability of mesenchymal stem cell (MSC) cluster from stromal vascular fraction (SVF). Experimental in vitro study on MSC culture derived from SVF. Biocompatibility was measured by viability of MSC from SVF with marker Propidium Iodine through flowcytometry. Electron microscope was used to assess the population density of MSC from SVF.